Brand RUCAS Campaign: Rhetorical Analysis and Dialectics in Sharia Perspective for Economic Empowerment - ST Monica Dwi M; Moch Chotib; Fauzan Fauzan (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2025)
Community economic empowerment through campaigns carried out by the RUCAS Brand is an interesting highlight because it presents a unique and inclusive marketing approach. This study aims to analyze the RUCAS Brand campaign from the perspective of rhetoric and dialectics within the framework of sharia values, especially in the context of economic empowerment of the lower strata community. The research method used in this study is a descriptive qualitative approach with data collection techniques carried out through participatory observation of campaign content on TikTok and Instagram, digital documentation in the form of downloading and archiving relevant content, and online literature studies from various trusted sources. Data analysis was carried out using rhetorical analysis, dialectical analysis, and sharia perspective approach. The results show that RUCAS brand campaigns are successful in creating persuasive and positive by combining elements of rhetoric and dialectics, they not only attract attention but also build an emotional connection with the audience. By providing opportunities for marginalized groups to participate in the creative economy and earn a decent income through endorsements, the RUCAS Brand carries out a socio-economic function in accordance with sharia principles.